Math, asked by manojshivhare30225, 7 months ago

please tell me answer ​

Attachments:

Answers

Answered by Asterinn
16

Given that :- r²+9r-36

We have to factorize the given expression.

=> r²+9r-36

Now to factorize the above expression, we will use middle term splitting method .

Now , 12r × (-3r)= - 36 r²

and 12r-3r = 9r

=> r² + 12r - 3r -36

=> r(r+ 12) - 3(r+12)

taking out (r+12) common.

=> (r+ 12) (r- 3)

Answer :

  • (r+ 12) (r- 3)

__________________

Additional Information :-

why do we factorize ?

=> We factorize to find out factors of a number. Any number can be presented or expressed in the form of its factor.

For example :-

1. Factors of 6 are 2 and 3.

Therefore , 6= 2×3

2. Factors of 7y are 7 and y.

Therefore , 7y = 7 × y

Similar questions